Bridging the Gap Between Applications and Networks in Data Centers - Costa, Paolo (ACM SIGOPS Operating Systems Review (OSR), 2013)
Modern data centers host tens (if not hundreds) of thousands of servers and are used by companies such as Amazon, Google, and Microsoft to provide online services to millions of individuals distributed across the Internet. They use commodity hardware and their network infrastructure adopts principles evolved from enterprise and Internet networking. Applications use UDP datagrams or TCP sockets as the primary interface to other applications running inside the data center. This eﬀectively isolates the network from the end-systems, which then have little control over how the network handles packets. Likewise, the network has limited visibility on the application logic. An application injects a packet with a destination address and the network just delivers the packet. Network and applications eﬀectively treat each other as black-boxes.